Daur al-Taḥawwul al-Raqmī wa al-Tiknūlūjiyā fī Taṭwīr wa Tanfīż al-Masyrū‘āt al-Mihaniyyah wa al-Riyādiyyah: Tajribah al-Jāmi‘āt al-‘Arabiyyah wa al-Ifrīqiyyah Namūżajan - M Alhawsawi, Akram Mahmoud (Study Program of Arabic Language Teaching, 2026)
This study aims to examine the role of digital transformation and emerging technologies in the development and implementation of professional and entrepreneurial projects within higher education institutions, with particular emphasis on the experiences of Arab and African universities. Specifically, the research investigates how digital technologies—including Artificial Intelligence (AI), Cloud Computing, and digital platforms—facilitate the transformation of academic research and innovative ideas into sustainable entrepreneurial ventures. It also analyzes the effectiveness of digital business incubators and institutional innovation ecosystems in promoting entrepreneurship and strengthening university–industry collaboration. The study employs a qualitative approach using descriptive-analytical and comparative methods. Data were collected through document analysis of academic publications, policy reports, institutional documents, and case studies from selected Arab and African universities. The collected data were analyzed through thematic content analysis to identify patterns, best practices, challenges, and strategic differences across the two regional contexts. The findings demonstrate that digital transformation has significantly enhanced universities' capacity to convert research outputs into market-oriented innovations by improving entrepreneurial ecosystems, facilitating technology transfer, and strengthening collaboration with industry and government stakeholders. The study also reveals that although Arab and African universities have made considerable progress in adopting digital entrepreneurship initiatives, they continue to face common challenges related to digital infrastructure, financial sustainability, technological readiness, institutional capacity, and digital competencies. Nevertheless, several universities have established successful models of innovation and entrepreneurship through digital incubators, technology parks, and AI-supported entrepreneurial programs.